Social balance model for Colombian community action boards (CAB) and similar Latin American organizations - Villalobos Garrido, Diego Fernando; Henao Guevara, Ingrid Suley (Cooperativismo & Desarrollo, 2017)
Introduction: The article presents a characterization of the conceptual and practical differences found in the community action boards (cab) and other similar organizations of the solidarity sector in Colombia. It continues with the cab concept comparison in different Latin American countries, and ends with the identification of the information that a social balance model should have for these organizations. Methodology: The research was descriptive. The methods applied were deduction, information systematization, and observation of a control group. Results: In order to validate the utility of the model, it was then applied to data obtained from the results gathered during 2015 in two cabs. This evidenced the management impact of these two cabs in the communities where they are present, and it was possible to calculate externalities and released resources. Conclusions: To reach a broader picture regarding the social balance model for cabs, it is important to incorporate some fundamental aspects, such as: effective democratic decision-making mechanisms (internal democracy), social integration mechanisms, redistribution, inclusion of vulnerabilities (social justice), and impacts achieved by cabs in the community’s social fabric (community social fabric construction), among other aspects.